2005
DOI: 10.1002/lt.20479
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamic and metabolic profiles in fulminant hepatic failure: Relationship to outcome

Abstract: The purpose of this retrospective study was to examine the potential role of cerebral hemodynamic and metabolic factors in the outcome of patients with fulminant hepatic failure (FHF). Based on the literature, a hypothetical model was proposed in which physiologic changes progress sequentially in five phases, as defined by intracranial pressure (ICP) and cerebral blood flow (CBF) measurements. Seventy-six cerebral physiologic profiles were obtained in 26 patients (2 to 5 studies each) within 6 days of FHF diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 34 publications
(50 reference statements)
3
33
0
2
Order By: Relevance
“…Aggarwal et al have described several stages in the evolution of the clinical picture of ALF with severe encephalopathy (9). Their observations note the importance of an increased cerebral blood flow (CBF) preceding the rise in ICP.…”
Section: B) Monitoring Cerebral Blood Flowmentioning
confidence: 99%
“…Aggarwal et al have described several stages in the evolution of the clinical picture of ALF with severe encephalopathy (9). Their observations note the importance of an increased cerebral blood flow (CBF) preceding the rise in ICP.…”
Section: B) Monitoring Cerebral Blood Flowmentioning
confidence: 99%
“…In the study, it was concluded that hyperemia alone was not related to the outcome, despite having occurred more frequently during elevated ICP. All patients with malignant intra cranial hypertension previously had hyperemia [62,63] . Nielsen et al [36] reported that both pressure and arterial oxygen saturation were maintained during infusion with norepinephrine.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%
“…Glucose is most frequently determined as the cellular energy substrate. In conditions where there is a decrease in both cerebral tissue glucose and PtiO2, a reduction of capillary blood flow may be inferred [63,64] . Lactate studies can indicate the intensity of anaerobic metabolism, while glycerol studies can evaluate tissue damage since glycerol is one of the structural components in the tissue lipid layer of cell membranes [66] .…”
Section: Metabolic Monitoringmentioning
confidence: 99%
“…Loss of auto-regulation [20] and cerebral hyperemia [21] are two common manifestations of ALF and encephalopathy. Systemic inflammatory response syndrome, particularly tumor necrosis factor has been shown to correlate with development of encephalopathy and raised intracranial pressure [22].…”
Section: Cerebral Blood Flowmentioning
confidence: 99%
“…Younger age, development of renal failure, hyponatremia, inflammatory response and the need for hemodynamic support for cardiovascular collapse are additional risk factors associated with the development of intracranial hypertension [24]. Similarly higher cerebral blood flow rates are seen in patients with cerebral edema and intracranial hypertension and are associated with higher mortality [21].…”
Section: Clinical Correlatesmentioning
confidence: 99%